Business model innovation influencing factors: an integrative literature review - Minatogawa, Vinicius Luiz Ferraz; Franco, Matheus Munhoz Vieira; Pinto, Jefferson de Souza; Batocchio, Antonio (Brazilian Journal of Operations & Production Management, 2018)
Highlights: Proposal to integrate the Business Model Innovation (BMI) influencing factors in a single framework. Twelve BMI influencing factors found through an integrative literature review. Factors grouped through an affinity diagram to design the framework architecture, containing four categories. The study highlights the importance for companies to consider the interrelationship between the influence factors to be successful in their BMI initiatives. Goal: This paper aims to provide an integrated framework that comprises influence factors for business model innovation, and describe them by exploring the linkages between different factors. Design / Methodology / Approach: an integrative literature review was conducted using PRISMA work flow to manage this kind of methodology. Results: This work finds 12 main potential influence factors for business model innovation. All factors have been grouped into four different categories, using the affinity diagram approach. Limitations of the investigation: Business model innovation is a recent research topic, and not all its influence factors are agreed upon. Despite the importance of grouping, those already described in a single framework, there may be other relevant factors not mapped. Originality / Value: Despite the existence of bibliographic material on specific influencing factors, there is, to the best of the authors’ knowledge, no study that integrates all the explored factors. This work contributes to literature by integrating the diverse factors into a single framework. Practical implications: It contributes to practice, enticing managers to reflect on their own environment, and on the possible paths to follow for succeeding with its business model innovations efforts.